Innovation Technology. A Dictionary - Schramm, Laurier (De Gruyter, 2017)
Innovation from A to Z presents a glossary, including: Terms, older terms whose meanings have changed, acronyms, synonyms, famous names, selected abbreviations, and cross-references. A highly interdisciplinary approach incorporating strategy and entrepreneurship with technology and engineering sciences, economics, marketing, organizational behavior and theory. Ideal for engineers, managers, sales people and economists.